Risk-informed multi-criteria assessment of dam reservoirs for floating photovoltaic farms in arid and semi-arid regions - Alireza Latif; Reza Javidi Sabbaghian; Mohammad Fereshtehpour (Discover Sustainability)
Abstract Floating Photovoltaic (FPV) farms have emerged as a rapidly advancing solar power technology, driven by land-use constraints and increasing global demand for sustainable energy solutions. This system has several advantages over land-based ones in terms of energy generation, water and land conservation, and environmental impacts. This study develops a risk-oriented decision-making framework to prioritize dams in Khorasan Razavi, Iran, for implementing FPV systems. To this end, the research employs the Fuzzy Analytic Hierarchy Process (FAHP) combined with risk attitudes related to multi-criteria satisfaction, to rank the selected dams. In addition, PVsyst software and the simplified Penman equation are used to analyze the potential for energy generation and evaporation reduction on these prioritized dams. In this study, three PV deployment scenarios are examined: floating PV arrays covering 1% and 10% of the reservoir’s surface area and a fixed 7 MW PV system as the feasible capacity under site-specific constraints. To guide the optimal deployment of FPV systems, this study introduces a point-based ranking framework that incorporates multiple risk perspectives—ranging from fully risk-averse to fully risk-prone scenarios. While results show consistency between the multi-criteria rankings and energy simulation outputs for several dams, notable discrepancies—such as Tabarak’s high risk-based rank despite its lower energy output and limited evaporation reduction—highlight the importance of using both approaches in tandem. The proposed framework contributes to a more comprehensive understanding of site suitability, balancing technical performance with broader contextual and stakeholder considerations. Graphical abstract